Influence of spontaneous curvature on the line tension of phase-coexisting domains in a lipid monolayer: A Landau-Ginzburg model - Rufeil Fiori, Elena; Downing, Rachel; Bossa, Guilherme Volpe [UNESP]; May, Sylvio (AIP Publishing, 2020)
The line tension between two coexisting phases of a binary lipid monolayer in its fluid state has contributions not only from the chemical mismatch energy between the two different lipid types but also from the elastic deformation of the lipid tails. We investigate to what extent differences in the spontaneous curvature of the two lipids affect the line tension. To this end, we supplement the standard Landau-Ginzburg model for the line tension between coexisting phases by an elastic energy that accounts for lipid splay and tilt. The spontaneous curvature of the two lipids enters into our model through the splay deformation energy. We calculate the structure of the interfacial region and the line tension between the coexisting domains numerically and analytically, the former based on the full non-linear model and the latter upon employing an approximation in the free energy that linearizes the resulting Euler-Lagrange equations. We demonstrate that our analytical approximation is in excellent agreement with the full non-linear model and use it to identify relevant length scales and two physical regimes of the interfacial profile, double-exponential decay, and damped oscillations. The dependence of the line tension on the spontaneous curvatures of the individual lipids is crucially dependent on how the bulk phases are affected. In the special case that the bulk phases remain inert, the line tension decreases when the difference between the spontaneous curvatures of the two lipid types grows.